SUPERCOMPUTERS FOR AIDING ECONOMIC PROCESSES WITH REFERENCE TO THE FINANCIAL SECTOR - Jerzy Balicki; Honorata Balicka; Waldemar Korłub; Jacek Paluszak; Marcin Zadroga (Contemporary Economy, 2014)
The article discusses the use of supercomputers to support business processes with particular emphasis on the financial sector. A reference was made to the selected projects that support economic development. In particular, we propose the use of supercomputers to perform artificial intel-ligence methods in banking. The proposed methods combined with modern technology enables a significant increase in the competitiveness of enterprises and banks by adding new functionality.